A global lending channel unplugged? Does U.S. monetary policy affect cross-border and affiliate lending by global U.S. banks? - Judit Temesvary; Steven Ongena; Ann L. Owen (Goethe University Frankfurt, Center for Financial Studies (CFS), 2015)
We examine how U.S. monetary policy affects the international activities of U.S. Banks. We access a rarely studied US bank-level dataset to assess at a quarterly frequency how changes in the U.S. Federal funds rate (before the crisis) and quantitative easing (after the onset of the crisis) affects changes in cross-border claims by U.S. banks across countries, maturities and sectors, and also affects changes in claims by their foreign affiliates. We find robust evidence consistent with the existence of a potent global bank lending channel. In response to changes in U.S. monetary conditions, U.S. banks strongly adjust their cross-border claims in both the pre and post-crisis period. However, we also find that U.S. bank affiliate claims respond mainly to host country monetary conditions
urn:nbn:de:hebis:30:3-382816
Keywords: E44; E52; F42; G15; G21; 330; bank lending channel; monetary transmission; global banking; cross-country analysis